2019
DOI: 10.1016/j.ejmech.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic titanocene-gold phosphane complexes inhibit invasion, metastasis, and angiogenesis-associated signaling molecules in renal cancer

Abstract: Following promising recent in vitro and in vivo studies of the anticancer efficacies of heterometallic titanocene–gold chemotherapeutic candidates against renal cancer, we report here on the synthesis, characterization, stability studies and biological evaluation of a new titanocene complex containing a gold-triethylphosphane fragment [(η-C5H5)2TiMe(μ-mba)Au(PEt3)] (4) Titanofin. The compound is more stable in physiological fluid than those previously reported, and it is highly cytotoxic against a line of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 83 publications
8
65
1
Order By: Relevance
“…An intriguing approach to exploit the distinct cytotoxic mechanism of action of Ti(IV) and Au(I) is synergizing their activity in the form of heterometallic compounds [115][116][117][118][119][120][121][122]. These compounds build off of the titanocene structure.…”
Section: Fusing the Auranofin And Titanocene Moieties To Create A Bimmentioning
confidence: 99%
“…An intriguing approach to exploit the distinct cytotoxic mechanism of action of Ti(IV) and Au(I) is synergizing their activity in the form of heterometallic compounds [115][116][117][118][119][120][121][122]. These compounds build off of the titanocene structure.…”
Section: Fusing the Auranofin And Titanocene Moieties To Create A Bimmentioning
confidence: 99%
“…Unexpectedly, NAMI‐A yielded less antimetastatic activity than Ru8 , suppressing the gap closure with 19.0 % at 32 μ m , which was comparable with the activity of Ru8 at 4 μ m (Figure 4 B). To eliminate the influence of cytotoxicity, the wound‐healing assay was further performed at low drug concentrations (e.g., IC 10 and IC 20 , Table S4) [31] . Encouragingly, Ru8 remained active against migration as compared to untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the influence of cytotoxicity,the wound-healing assayw as further performed at low drug concentrations (e.g.,I C 10 and IC 20 ,T able S4). [31] En- couragingly, Ru8 remained active against migration as compared to untreated cells. However, at the concentrations of IC 10 or IC 20 ,N AMI-A failed to inhibit the gap closure in the cells (Figure S30).…”
Section: In Vitro Antimetastatic Activitymentioning
confidence: 93%
“…The incorporation of the PEt 3 auxiliary ligand was motivated by the activity observed for the Au‐PEt 3 fragment of Auranofin. Extensive in vitro studies revealed that both 98 and 104 (Figure ), inhibit cell migration, proliferation and angiogenesis, as well as the inhibition of TrxR and VEGF (vascular endothelial growth factor) …”
Section: Goldmentioning
confidence: 99%